A method for recycling positive electrode active material using magnesium sulfate
Through the method of recycling the positive electrode active material by magnesium sulfate, the problems of low lithium recovery rate and high energy consumption in lithium-ion battery recycling are solved, efficient recycling and recycling are achieved, the process is simplified and environmental impact is reduced.
Patent Information
- Application Number
- CN202510050166.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing lithium-ion battery recycling technology has problems such as low lithium recovery rate, high energy consumption, difficult subsequent alloy refining, and large amounts of waste liquid, making it difficult to achieve resource recycling and sustainable development.
The method of recycling the positive electrode active material by magnesium sulfate is adopted to recover lithium through the vulcanization reduction and calcination and water immersion steps, and the magnesium sulfate is recovered through dilute sulfuric acid to achieve recycling and reuse, and finally obtain the regenerated positive electrode active material through sintering.
It realizes efficient lithium recycling (recovery rate reaches more than 99%), reduces the consumption of chemical reagents and waste liquid generation, simplifies the metal recycling process, and improves the recovery and utilization rate of recycled ternary cathode materials.
Smart Images

Figure CN119481410B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of positive electrode active material recovery, and in particular relates to a method for recycling positive electrode active materials by utilizing magnesium sulfate. Background Art
[0002] With the booming development of the electric vehicle industry, a large number of lithium-ion batteries are gradually scrapped after 5 to 8 years of use, which has led to the practical issue of how to efficiently recycle the valuable metals in them. x Co y Mn 1~x~y As a widely used ternary cathode material, lithium (Li), nickel (Ni), cobalt (Co) and manganese (Mn) are highly favored due to their high energy density and excellent comprehensive performance. However, the reuse of key elements such as lithium (Li), nickel (Ni), cobalt (Co) and manganese (Mn) contained in waste lithium batteries is a key link in achieving resource recycling and sustainable development. If not handled properly, it will not only waste precious resources, but also have potential impacts on the environment.
[0003] The current industrial process for recycling used lithium batteries includes disassembly and enrichment in the early stages, using mechanical crushing and sorting to remove external structural materials such as plastic, iron, aluminum, and copper, and relatively concentrate the positive and negative active materials to obtain "black powder" containing a large amount of positive active materials, graphite, and a small amount of impurity metals. For this mixture, the subsequent commonly used processing routes are mainly divided into two categories: hydrometallurgy and pyrometallurgy.
[0004] Hydrometallurgical technology is currently the main industrial recycling method in China. Usually, a combination of sulfuric acid and hydrogen peroxide is used in the acid leaching process to dissolve lithium, nickel, cobalt, manganese and other metals into the leachate, and then the metals are recovered step by step through precipitation, solvent extraction, ion exchange and other methods. The investment threshold of this technology is relatively low, the metal dissolution rate is high, and resource recovery can be achieved well. However, the simultaneous entry of all metals into the solution means that the subsequent separation and purification process will become complicated and time-consuming. In addition, the large consumption of chemical reagents such as acids and alkalis and the discharge of waste liquids also bring dual pressures on environmental management and economic costs.
[0005] With the further increase in the number of waste batteries, pyrometallurgy has gradually become a hot topic. This technology has the advantages of large processing capacity, relatively short process, and strong adaptability to different types of scrapped batteries. Although pyrometallurgical technology is relatively mature, it still faces a series of difficulties. First, lithium is easily combined with oxygen and is usually trapped in the slag phase in the form of oxides at high temperatures, resulting in a low lithium recovery rate. Secondly, in order to fully melt nickel and cobalt, the smelting temperature often needs to be higher than 1500°C, which means high energy consumption and operating costs. In addition, although the Ni-Co alloy obtained by pyrometallurgy has a high metal content, its high mechanical strength and corrosion resistance also increase the difficulty of subsequent crushing, dissolution and refining, and it is often necessary to combine wet processes for further purification and separation.
[0006] From the above analysis, it can be seen that the traditional pyrometallurgical method has limitations in lithium recovery rate, energy utilization efficiency and subsequent alloy refining; and although hydrometallurgy can achieve a high metal dissolution rate at room temperature, it requires a cumbersome multi-step separation and purification process and produces a large amount of waste liquid. Therefore, a new process that can simplify the metal recovery process, reduce material and energy consumption, and improve metal recovery rate and utilization rate is needed to meet the above challenges. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention provides a method for recycling positive electrode active materials by using magnesium sulfate, aiming to carry out sulfidation reduction roasting on waste lithium battery black powder by magnesium sulfate, and achieve the purpose of recovering Li in combination with a water leaching step, and then use dilute sulfuric acid to recover magnesium sulfate from the water leaching residue to achieve recycling, and the obtained acid leaching residue and the recovered Li are re-proportioned and sintered to simultaneously achieve the regeneration of positive electrode active materials.
[0008] In order to achieve the above object, the present invention provides a method for recycling positive electrode active materials using magnesium sulfate, comprising the following steps:
[0009] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon source according to n (Me) :n (MgSO4) :n (C) =1:1.2~1.8:1.8~2.5 for mixing, where n (Me) The total molar amount of nickel, cobalt and manganese in the waste lithium battery black powder is then placed in a vacuum or inert atmosphere for roasting to obtain a roasted product, wherein the waste lithium battery black powder is a black or gray-black powder composed of metal elements such as nickel, cobalt, manganese and lithium and non-metallic elements such as carbon and oxygen obtained by a series of pretreatment processes of waste lithium-ion batteries; the roasting temperature is 600-900° C. When the carbon content in the waste lithium battery black powder meets the ratio requirements, the amount of carbon source added is 0;
[0010] 2) adding the roasted product obtained in step 1) into water at a mass volume ratio of roasted product: water = 1:5-1:15 g / mL for water leaching treatment, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0011] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution to precipitate lithium until the lithium carbonate is completely precipitated, thereby obtaining lithium carbonate precipitate and recovering metallic lithium. In this step, the saturated sodium carbonate solution should be kept in excess to ensure that the lithium sulfate can be fully converted into lithium carbonate precipitate;
[0012] 4) drying the water leaching residue obtained in step 2), adding dilute sulfuric acid for acid leaching, filtering to obtain the acid leaching residue and magnesium sulfate solution, and then evaporating and crystallizing the magnesium sulfate solution to obtain magnesium sulfate precipitate, thus realizing the magnesium sulfate recovery cycle;
[0013] 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3), and the mixture is sintered to obtain the regenerated ternary positive electrode active material.
[0014] It should be noted that the waste lithium battery black powder in the present invention refers to a black or gray-black powder composed of metal elements such as nickel, cobalt, manganese, lithium and non-metallic elements such as carbon and oxygen obtained after the waste lithium-ion batteries have undergone a common physical pretreatment process in the field. In the present invention, the waste lithium battery black powder with the same composition and content will not affect the relevant technical effects of the present invention even if it undergoes different physical pretreatment processes.
[0015] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in the step 1), the components of the waste lithium battery black powder include, by mass: Ni: 15-80%, Co: 5-30%, Mn: 5-30%, Li: 2-10%, Al: 0-1%, Ca: 0-0.3%, Mg: 0-0.3%, Fe: 0-0.3%, Cu: 0-1%, and C: 0-35%.
[0016] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in the step 1), the calcination time is 1 to 3 hours.
[0017] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in the step 2), the water immersion treatment is performed for 1 to 3 hours at a temperature of 20 to 40°C.
[0018] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in step 3), the concentration of saturated sodium carbonate is 1.5-2 mol / L.
[0019] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in the step 4), the acid leaching treatment time is 1-3 hours and the temperature is 40-80°C.
[0020] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in step 4), the concentration of the dilute sulfuric acid is 0.2-0.6 mol / L, and the amount of the dilute sulfuric acid added is based on the concentration of n in the acid leaching residue after acid leaching. (Me) :n (Mg) =1:0.02~1:0.05, where n (Me) is the total molar amount of nickel, cobalt and manganese in the acid leaching residue. The amount of dilute sulfuric acid added can be adjusted by adding multiple times according to the residual magnesium content in the acid leaching residue after acid leaching.
[0021] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in the step 5), the acid leaching residue obtained in the step 4) and the lithium carbonate obtained in the step 3) are mixed according to the molar ratio of Li:Ni:Co:Mn:Mg=1~1.1:0.5:0.2:0.3:0.02~0.05. When the content of Ni, Co and / or Mn is insufficient, it can be supplemented by adding nickel sulfate, cobalt sulfate and / or manganese sulfate.
[0022] According to a preferred embodiment of the method for recycling positive electrode active materials using magnesium sulfate of the present invention, in the step 5), the sintering atmosphere is an oxygen atmosphere, and the sintering is first performed at 750-800°C for not less than 5 hours, and then the temperature is raised to 900-950°C and sintered for not less than 20 hours.
[0023] The present invention creatively finds that, compared with the sulfidation reduction roasting of the traditional carbon-sulfur system, the use of the carbon-sulfate system for sulfidation reduction roasting can significantly optimize the reaction sequence and promote the sulfation of lithium. In the traditional carbon-sulfur system, the sulfidation process of the metal is carried out in sequence, and with the addition of sulfur, the sulfidation order of the metal is nickel, cobalt, manganese, and lithium. This order often leads to insufficient sulfidation of lithium, generating a mixture of various lithium salts such as lithium sulfate, lithium sulfide, lithium carbonate, and lithium oxide, which increases the complexity of subsequent separation and purification. In contrast, in the carbon-sulfate system, since the sulfate ion has two lithium-philic sites, the sulfidation of lithium can take precedence over the sulfidation of cobalt and manganese, and the conversion is more complete and thorough, generating only a single lithium sulfate. This not only improves the conversion efficiency of lithium, but also simplifies the subsequent separation and purification process, avoids the generation of a variety of lithium salt mixtures, and is conducive to efficient and simple metal recovery and purification. Therefore, the carbon-sulfate system shows significant advantages in the sulfidation reduction roasting process, which helps to improve the efficiency and economy of the overall recovery process.
[0024] The present invention creatively finds that, compared with other sulfates such as calcium sulfate, ammonium sulfate, sodium sulfate or sodium bisulfate, magnesium sulfate can not only decompose and release sulfate ions at a lower roasting temperature, but also the magnesium oxide generated after decomposition can be reconverted into water-soluble magnesium sulfate during the subsequent dilute sulfuric acid leaching, thereby realizing recycling; while calcium sulfate, due to the narrow temperature application range of the sulfidation roasting stage, often exists in the form of calcium oxide, calcium carbonate and residual calcium sulfate after roasting, and in the subsequent acid leaching process, the calcium sulfate generated by it has low solubility and is difficult to react with Ni , Co, and Mn sulfides can be effectively separated, and calcium carbonate or calcium oxide is a commonly used slag-forming agent in nickel metallurgy. Therefore, calcium sulfate is used for recovery, which is more suitable for subsequent slag smelting. If ammonium sulfate is used, the ammonium radical is easily converted into ammonia volatilization or enters the water leaching liquid in the form of sulfate, which is difficult to further separate and purify for recycling. As for sodium sulfate or sodium bisulfate, the sulfidation ability of Ni, Co, and Mn is relatively poor, and it mainly enters the water phase in the form of sodium salt. The subsequent purification and separation is also complicated and the purity is difficult to guarantee, so effective recycling cannot be achieved. In order to obtain the ideal recovery effect of metallic lithium and magnesium, the present invention limits the amount of n in the waste lithium battery black powder when mixing the ingredients. (Me) With n (MgSO4) The ratio is 1:1.2~1.8, where n (Me) It is the total molar amount of nickel, cobalt and manganese in the black powder of waste lithium battery. This is because, if the ratio of the two is higher than 1:1.2, Ni, Co and Mn in the black powder cannot be fully sulfided, and some residues will exist in the solid phase in the form of oxides, which will enter the acid leaching solution together with Mg in the subsequent acid leaching process, thus affecting the recovery purity and recovery efficiency of magnesium sulfate; if the ratio of the two is lower than 1:1.8, excess magnesium sulfate may dissolve in the water leaching solution, thereby affecting the recovery effect of lithium and causing waste of magnesium.
[0025] The present invention creatively discovered that the introduction of an appropriate amount of carbon during the roasting process helps to lower the temperature threshold of the sulfidation reaction, thereby improving the sulfidation efficiency. This is because, compared with high-valent metal oxides, metals or low-valent metal oxides are more susceptible to sulfidation reactions. During the sulfidation reduction roasting process of the positive electrode material, carbon will first combine with oxygen to reduce the valence of metal atoms near oxygen, thereby promoting the sulfidation process of transition metals. In addition, an appropriate amount of carbon can enhance the selectivity of the sulfidation reaction, prompting transition metals such as nickel and cobalt to be effectively converted into metal sulfides that are insoluble in water and dilute sulfuric acid, which is convenient for subsequent recovery. However, the control of carbon content is crucial. When the carbon content in the waste lithium battery black powder is insufficient, nickel, cobalt and manganese cannot be fully sulfided, and some metals will exist in the form of acid-soluble oxides, affecting their recovery effect. On the contrary, if the carbon content is too high, excess carbon will cause lithium sulfate to decompose to form lithium sulfide, which may not only reduce the recovery rate of lithium, but also hydrolyze in the air to produce toxic hydrogen sulfide gas. At the same time, too much carbon will also inhibit the sulfidation reaction of nickel and cobalt, adding additional costs. Taking the above factors into consideration, the present invention adjusts the molar total amount of nickel, cobalt and manganese in the waste lithium battery black powder, the molar ratio of magnesium sulfate and carbon source to n (Me) :n (MgSO4) :n (C) It is optimized to 1:1.2~1.8:1.8~2.5 to achieve a reasonable balance between process conditions and costs while ensuring efficient recovery of lithium, nickel, cobalt and manganese. The carbon can be supplemented by adding carbon powder according to the difference in carbon content in the black powder of waste lithium battery.
[0026] The present invention creatively discovered that an appropriate amount of Mg doping can significantly improve the structure and cycle performance of the regenerated ternary cathode material. After Mg ions occupy part of the Li sites, they can effectively inhibit the mixed arrangement of cations and the disordered migration of Li ions, enhance the stability of the layered structure of the material, reduce the amplitude of the change of the lattice during the cycle, and slow down the occurrence of side reactions between high-valent transition metals and electrolytes, thereby reducing the accumulation of interface byproducts and the increase of impedance, and promoting Li + The diffusion dynamics of Mg can improve the cycle life of the material. However, the Mg doping amount needs to be carefully controlled. If the Mg content is too high, it will occupy too many Li sites, reduce the amount of reversible lithium ion deintercalation, lead to a decrease in capacity and coulombic efficiency, and weaken the integrity of the layered structure to a certain extent. At the same time, the introduction of excessive Mg is not only difficult to further improve the cycle stability, but will lead to a decrease in the specific capacity and performance degradation of the regenerated ternary positive electrode active material. In order to ensure excellent cycle stability while maintaining a high reversible capacity, the optimized doping ratio of the present invention controls the molar ratio of the total amount of nickel, cobalt and manganese in the acid leaching residue to the amount of Mg in 1:0.02~0.05, successfully achieving a balance between performance and stability.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention uses magnesium sulfate to perform sulfide reduction roasting on waste positive electrode materials in a relatively low temperature range of 600 to 900°C, so that the lithium element exists in the form of easily soluble lithium sulfate, thereby directly realizing efficient lithium recovery in the subsequent water leaching process. The lithium recovery rate obtained based on the technical solution of the present invention reaches more than 99%.
[0029] 2. The present invention can avoid the loss of important elements such as nickel, cobalt, and manganese during the regeneration process through reasonable raw material ratios and process parameter control. It has been determined that the nickel recovery rate of the regenerated ternary positive electrode material obtained based on the technical solution of the present invention is more than 99%, the cobalt recovery rate is more than 98%, and the manganese recovery rate is more than 97%.
[0030] 3. The present invention realizes the recycling of magnesium sulfate, reduces the consumption of chemical reagents and secondary pollution, and through the reasonable design of the acid leaching step, magnesium oxide is converted into magnesium sulfate solution and then magnesium sulfate is recovered by evaporation and crystallization, thereby forming a closed loop within the system, which not only effectively reduces the cost of regenerating ternary positive electrode active materials, but also reduces the generation of waste liquid and solid waste. The purity of magnesium sulfate recovered based on the technical solution of the present invention reaches more than 96%, and it can be recycled again without other treatment.
[0031] 4. The present invention also doped an appropriate amount of magnesium in the regeneration process, combined with the process parameter control of acid leaching and regeneration process, so that magnesium exists in the regenerated NCM ternary positive electrode material at an appropriate concentration and occupies a certain Li site. This doping strategy improves the layered structure of the regenerated ternary positive electrode material, inhibits cation mixing, reduces the lattice change amplitude, and reduces interface side reactions and impedance growth. The optimized Mg doping amount can maintain a high reversible capacity and coulomb efficiency as much as possible while improving the cycle stability. It has been determined that the regenerated ternary positive electrode material obtained by the technical solution of the present invention has an initial discharge specific capacity of more than 160 mAh / g at a current rate of 0.2C, and remains above 140 mAh / g after 100 cycles. The coulomb efficiency is stable at more than 90% during the cycle, reflecting good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The reaction flow chart of the present invention is DETAILED DESCRIPTION
[0033] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that in the embodiments and comparative examples of the present invention, the recovery rate of metal elements = the mass of metal elements in the recovered product / the mass of metal elements in the raw material.
[0035] Example 1
[0036] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0037] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.5:2.4; the components of the waste lithium battery black powder include (by mass): Ni: 25.63%, Co: 10.62%, Mn: 15.54%, Li: 6.67%, Al: 0.73%, Cu: 0.03%, C: 17.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 850°C for 2 hours to obtain a roasted product;
[0038] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0039] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.21%;
[0040] 4) After drying the water leaching residue obtained in step 2), first calculate and determine the amount of magnesium oxide to be retained based on the molar ratio of the total amount of nickel, cobalt and manganese in the target acid leaching residue after acid leaching to magnesium (1:0.03). Subsequently, add 0.4 mol / L of dilute sulfuric acid at 60°C and perform acid leaching adjustment for 2 hours; after filtration, obtain the acid leaching residue and magnesium sulfate solution that retain part of the magnesium oxide. Finally, the obtained magnesium sulfate solution is subjected to an evaporation and crystallization treatment to obtain a magnesium sulfate precipitate with a purity of 98.34%, thereby realizing the recovery and recycling of magnesium sulfate;
[0041] 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3) according to the molar ratio of Li:Ni:Co:Mn:Mg=1.05:0.5:0.2:0.3:0.03. At this time, the Ni content in the acid leaching residue is insufficient, and a small amount of nickel sulfate needs to be added to meet the above ratio. Then, in an oxygen atmosphere, it is pre-sintered at 750°C for 5h, and then heated to 900°C and sintered for 20h to obtain the regenerated ternary positive electrode active material.
[0042] It has been determined that the nickel recovery rate in this embodiment is 99.15%, the cobalt recovery rate is 99.02%, and the manganese recovery rate is 98.36%. At a current rate of 0.2C, the initial discharge specific capacity of the regenerated ternary positive electrode active material is 163.97mAh / g, and it remains at 142.54mAh / g after 100 cycles. The coulombic efficiency is stable at 91.36% during the cycle.
[0043] Example 2
[0044] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0045] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.8:2.4. The components of the waste lithium battery black powder include: Ni: 26.03%, Co: 10.89%, Mn: 15.21%, Li: 6.72%, Al: 0.88%, Cu: 0.02%, Mg: 0.01%, C: 15.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast at 850°C for 2 hours to obtain a roasted product;
[0046] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0047] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.16%;
[0048] 4) After drying the water leaching residue obtained in step 2), first calculate and determine the amount of magnesium oxide to be retained based on the molar ratio of the total amount of nickel, cobalt and manganese in the target acid leaching residue after acid leaching to magnesium (1:0.03). Subsequently, add 0.4 mol / L of dilute sulfuric acid at 60°C and perform acid leaching adjustment for 2 hours; after filtering, obtain the acid leaching residue and magnesium sulfate solution that retain part of the magnesium oxide. Finally, the obtained magnesium sulfate solution is subjected to an evaporation and crystallization treatment to obtain a magnesium sulfate precipitate with a purity of 98.25%, thereby realizing the recovery and recycling of magnesium sulfate;
[0049] 5) The acid leaching residue obtained in step 4) and the lithium carbonate obtained in step 3) are mixed according to the molar ratio of Li:Ni:Co:Mn:Mg=1.05:0.5:0.2:0.3:0.03. Due to the insufficient Ni content in the acid leaching residue, a small amount of nickel sulfate is required to meet the above ratio. Then, in an oxygen atmosphere, pre-sintering is performed at 750°C for 5 hours, and then the temperature is raised to 900°C and sintered for 20 hours to obtain the regenerated ternary positive electrode active material.
[0050] It has been determined that the nickel recovery rate in this embodiment is 99.17%, the cobalt recovery rate is 98.96%, and the manganese recovery rate is 98.54%. At a current rate of 0.2C, the initial discharge specific capacity of the regenerated ternary positive electrode active material is 162.86mAh / g, and it remains at 143.02mAh / g after 100 cycles. The coulombic efficiency is stable at 91.43% during the cycle.
[0051] Example 3
[0052] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0053] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.5:1.8. The components of the waste lithium battery black powder include: Ni: 26.72%, Co: 11.01%, Mn: 15.65%, Li: 6.81%, Al: 0.56%, Cu: 0.03%, Fe: 0.01%, C: 17.96%. Since the carbon content in the waste lithium battery black powder is sufficient, there is no need to add additional carbon powder. Then place the mixture in a vacuum atmosphere and roast it at 850°C for 2 hours to obtain a roasted product;
[0054] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0055] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.22%;
[0056] 4) After drying the water leaching residue obtained in step 2), first calculate and determine the amount of magnesium oxide to be retained based on the molar ratio of the total amount of nickel, cobalt and manganese in the target acid leaching residue after acid leaching to magnesium (1:0.03). Subsequently, add 0.4 mol / L of dilute sulfuric acid at 60°C and perform acid leaching adjustment for 2 hours; after filtration, obtain the acid leaching residue and magnesium sulfate solution that retain part of the magnesium oxide. Finally, the obtained magnesium sulfate solution is subjected to an evaporation and crystallization treatment to obtain a magnesium sulfate precipitate with a purity of 96.26%, thereby realizing the recovery and recycling of magnesium sulfate;
[0057] 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3) according to the molar ratio of Li:Ni:Co:Mn:Mg=1.05:0.5:0.2:0.3:0.03. At this time, the Ni content in the acid leaching residue is insufficient, and a small amount of nickel sulfate needs to be added to meet the above ratio. Then, in an oxygen atmosphere, it is pre-sintered at 750°C for 5h, and then heated to 900°C and sintered for 20h to obtain the regenerated ternary positive electrode active material.
[0058] It has been determined that the nickel recovery rate in this embodiment is 99.02%, the cobalt recovery rate is 98.04%, and the manganese recovery rate is 97.17%. At a current rate of 0.2C, the initial discharge specific capacity of the regenerated ternary positive electrode active material is 162.21mAh / g, and it remains at 142.28mAh / g after 100 cycles. The coulombic efficiency is stable at 91.64% during the cycle.
[0059] Example 4
[0060] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0061] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.5:2.4. The components of the waste lithium battery black powder include: Ni: 26.59%, Co: 10.58%, Mn: 15.38%, Li: 6.76%, Al: 0.82%, Cu: 0.04%, Ca: 0.01%, C: 17.25%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast at 650°C for 2 hours to obtain a roasted product;
[0062] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0063] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.07%;
[0064] 4) After drying the water leaching residue obtained in step 2), first calculate and determine the amount of magnesium oxide to be retained based on the molar ratio of the total amount of nickel, cobalt and manganese in the target acid leaching residue after acid leaching to magnesium (1:0.03). Subsequently, add 0.4 mol / L of dilute sulfuric acid at 60°C and perform acid leaching adjustment for 2 hours; after filtering, obtain the acid leaching residue and magnesium sulfate solution that retain part of the magnesium oxide. Finally, the obtained magnesium sulfate solution is subjected to an evaporation and crystallization treatment to obtain a magnesium sulfate precipitate with a purity of 98.17%, thereby realizing the recovery and recycling of magnesium sulfate;
[0065] 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3) in a molar ratio of Li:Ni:Co:Mn:Mg=1.05:0.5:0.2:0.3:0.03. Since the content of each element meets the above-mentioned ratio conditions, no sulfate needs to be added in this step. Then, in an oxygen atmosphere, the mixture is pre-sintered at 750°C for 5h, and then heated to 900°C and sintered for 20h to obtain the regenerated ternary positive electrode active material.
[0066] It has been determined that the nickel recovery rate in this embodiment is 99.03%, the cobalt recovery rate is 98.99%, and the manganese recovery rate is 98.14%. At a current rate of 0.2C, the initial discharge specific capacity of the regenerated ternary positive electrode active material is 161.87mAh / g, and it remains at 141.96mAh / g after 100 cycles. The coulombic efficiency is stable at 91.14% during the cycle.
[0067] Example 5
[0068] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0069] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.5:2.4. The components of the waste lithium battery black powder include: Ni: 26.33%, Co: 10.25%, Mn: 15.15%, Li: 6.69%, Al: 0.44%, Cu: 0.02, C: 17.33%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 850°C for 2 hours to obtain a roasted product;
[0070] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0071] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.31%;
[0072] 4) After drying the water leaching residue obtained in step 2), first calculate and determine the amount of magnesium oxide to be retained based on the molar ratio of the total amount of nickel, cobalt and manganese in the target acid leaching residue after acid leaching to magnesium (1:0.05). Subsequently, add 0.4 mol / L of dilute sulfuric acid at 60°C and perform acid leaching adjustment for 2 hours; after filtration, obtain the acid leaching residue and magnesium sulfate solution that retain part of the magnesium oxide. Finally, the obtained magnesium sulfate solution is subjected to an evaporation and crystallization treatment to obtain a magnesium sulfate precipitate with a purity of 98.46%, thereby realizing the recovery and recycling of magnesium sulfate;
[0073] 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3) according to the molar ratio of Li:Ni:Co:Mn:Mg=1.05:0.5:0.2:0.3:0.05. At this time, the Co content in the acid leaching residue is insufficient, and a small amount of cobalt sulfate needs to be added to meet the above ratio. Then, in an oxygen atmosphere, it is pre-sintered at 750°C for 5h, and then heated to 900°C and sintered for 20h to obtain the regenerated ternary positive electrode active material.
[0074] It has been determined that the nickel recovery rate in this embodiment is 99.27%, the cobalt recovery rate is 98.93%, and the manganese recovery rate is 98.57%. At a current rate of 0.2C, the initial discharge specific capacity of the regenerated ternary positive electrode active material is 160.03mAh / g, and it remains at 144.08mAh / g after 100 cycles. The coulombic efficiency is stable at 90.02% during the cycle.
[0075] Comparative Example 1
[0076] A method for recycling positive electrode active materials using calcium sulfate comprises the following steps:
[0077] 1) Mix the waste lithium battery black powder, calcium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: calcium sulfate: carbon = 1:1.5:2.4. The components of the waste lithium battery black powder include (by mass): Ni: 25.63%, Co: 10.62%, Mn: 15.54%, Li: 6.67%, Al: 0.73%, Cu: 0.03%, C: 17.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 800°C for 2h to obtain a roasted product;
[0078] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0079] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.28%;
[0080] 4) Dry the leached residue obtained in step 2) and add 0.4 mol / L dilute sulfuric acid for acid leaching at 60°C for 2 hours. Since the calcium sulfate generated after acid leaching is slightly soluble in water and cannot be effectively separated from the sulfides of nickel, cobalt and manganese, the calcium sulfate cannot be effectively recovered, and subsequent positive electrode regeneration cannot be performed.
[0081] Comparative Example 2
[0082] A method for recycling positive electrode active materials using sodium sulfate comprises the following steps:
[0083] 1) Mix the waste lithium battery black powder, sodium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: sodium sulfate: carbon = 1:1.5:2.4. The components of the waste lithium battery black powder include (by mass): Ni: 25.63%, Co: 10.62%, Mn: 15.54%, Li: 6.67%, Al: 0.73%, Cu: 0.03%, C: 17.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 800°C for 2 hours to obtain a roasted product;
[0084] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0085] 3) The lithium sulfate solution obtained in step 2) is gradually added to a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. It has been determined that the recovery rate of metallic lithium is 99.17%.
[0086] However, due to the insufficient sulfidation capacity of sodium sulfate, nickel, cobalt and manganese cannot be fully sulfided during the roasting process, resulting in some metals still existing in the form of oxides; during the acid leaching stage, these oxides will be converted into sulfates and enter the liquid phase, greatly increasing the difficulty and complexity of nickel, cobalt and manganese recovery. In addition, the products generated by sodium sulfate after roasting are lost with the liquid phase during the first water leaching, and can hardly be recovered during the acid leaching stage. Therefore, the use of sodium sulfate can neither achieve the subsequent effective recovery of nickel, cobalt and manganese and the regeneration of the positive electrode, nor can it effectively recover sodium sulfate for recycling.
[0087] Comparative Example 3
[0088] A method for recycling positive electrode active materials using ammonium sulfate comprises the following steps:
[0089] 1) Mix the waste lithium battery black powder, ammonium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: ammonium sulfate: carbon = 1:1.5:2.4. The components of the waste lithium battery black powder include (by mass): Ni: 25.63%, Co: 10.62%, Mn: 15.54%, Li: 6.67%, Al: 0.73%, Cu: 0.03%, C: 17.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 800°C for 2 hours to obtain a roasted product;
[0090] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0091] 3) The lithium sulfate solution obtained in step 2) is gradually added to a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. It has been determined that the recovery rate of metallic lithium is 99.20%.
[0092] However, due to the insufficient sulfidation capacity of ammonium sulfate, nickel, cobalt and manganese cannot be fully sulfided during the roasting process, resulting in some metals still existing in the form of oxides; during the acid leaching stage, these oxides will be converted into sulfates and enter the liquid phase, greatly increasing the difficulty and complexity of nickel, cobalt and manganese recovery. In addition, the ammonium ions in ammonium sulfate are mainly lost in the form of ammonia gas during the roasting stage and can hardly be recovered during the acid leaching stage. Therefore, the use of ammonium sulfate can neither achieve the subsequent effective recovery of nickel, cobalt and manganese and the regeneration of the positive electrode, nor can it effectively recover ammonium sulfate for recycling.
[0093] Comparative Example 4
[0094] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0095] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:0.5:2.4. The components of the waste lithium battery black powder include (by mass): Ni: 25.63%, Co: 10.62%, Mn: 15.54%, Li: 6.67%, Al: 0.73%, Cu: 0.03%, C: 17.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 850°C for 2 hours to obtain a roasted product;
[0096] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0097] 3) The lithium sulfate solution obtained in step 2) is gradually added to a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. It has been determined that the recovery rate of metallic lithium is 69.38%.
[0098] However, due to the insufficient addition of magnesium sulfate, nickel, cobalt and manganese cannot be fully sulfided, and nickel, cobalt and manganese cannot be subsequently recovered according to this technical route. Moreover, at this amount of magnesium sulfate added, most of the nickel and cobalt exist in the form of elements, while manganese mainly exists in the form of manganese oxide. Therefore, it is also impossible to use acid leaching to recover magnesium sulfate for recycling.
[0099] Comparative Example 5
[0100] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0101] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.5:0.5. The components of the waste lithium battery black powder include (by mass): Ni: 29.76%, Co: 12.15%, Mn: 18.21%, Li: 6.98%, Al: 0.86%, Cu: 0.04%, C: 2.33%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 850°C for 2 hours to obtain a roasted product;
[0102] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0103] 3) The lithium sulfate solution obtained in step 2) is gradually added to a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. It has been determined that the recovery rate of metallic lithium is 90.25%.
[0104] However, due to insufficient carbon addition, nickel, cobalt and manganese cannot be fully sulfided and subsequently recovered according to this technical route. Moreover, at this carbon addition amount, most of the nickel, cobalt and manganese exist in the form of oxides, so acid leaching cannot be used to recover magnesium sulfate for recycling.
[0105] Comparative Example 6
[0106] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0107] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.5:2.4. The components of the waste lithium battery black powder include (by mass): Ni: 25.63%, Co: 10.62%, Mn: 15.54%, Li: 6.67%, Al: 0.73%, Cu: 0.03%, C: 17.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 850°C for 2 hours to obtain a roasted product;
[0108] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0109] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.19%;
[0110] 4) After drying the water leaching residue obtained in step 2), in order to completely remove the magnesium oxide therein, 0.4 mol / L dilute sulfuric acid was added at 60°C and acid leaching was carried out for 2 hours. The acid leaching residue and magnesium sulfate solution were collected after filtration, and the obtained magnesium sulfate solution was evaporated and crystallized to obtain magnesium sulfate precipitate with a purity of 98.31%, thereby realizing the recovery and recycling of magnesium sulfate;
[0111] 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3) according to the molar ratio of Li:Ni:Co:Mn = 1.05:0.5:0.2:0.3. At this time, the Ni content in the acid leaching residue is insufficient, and a small amount of nickel sulfate needs to be added to meet the above ratio. Then, in an oxygen atmosphere, it is pre-sintered at 750°C for 5h, and then heated to 900°C and sintered for 20h to obtain the regenerated ternary positive electrode active material.
[0112] It has been determined that the nickel recovery rate in this embodiment is 99.18%, the cobalt recovery rate is 98.99%, and the manganese recovery rate is 98.32%. At a current rate of 0.2C, the initial discharge specific capacity of the regenerated ternary positive electrode active material is 170.87mAh / g, but after 100 cycles it is only 120.43mAh / g, and the coulombic efficiency during the cycle is 94.76%.
[0113] Comparative Example 7
[0114] A method for recycling positive electrode active materials using magnesium sulfate comprises the following steps:
[0115] 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon powder according to the molar ratio of the total amount of nickel, cobalt and manganese in the black powder: magnesium sulfate: carbon = 1:1.5:2.4. The components of the waste lithium battery black powder include (by mass): Ni: 25.63%, Co: 10.62%, Mn: 15.54%, Li: 6.67%, Al: 0.73%, Cu: 0.03%, C: 17.63%. At this time, the carbon content in the waste lithium battery black powder is insufficient, and additional carbon powder needs to be added to meet the above ratio. Then place the mixture in an argon atmosphere and roast it at 850°C for 2 hours to obtain a roasted product;
[0116] 2) adding water to the calcined product obtained in step 1) at a mass volume ratio of calcined product: water = 1:10 g / mL, and performing water leaching treatment at 25° C. for 2 h, and obtaining a lithium sulfate solution and water leaching residue after suction filtration;
[0117] 3) gradually adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution with a concentration of 2 mol / L to precipitate lithium until the lithium sulfate is fully converted into lithium carbonate precipitate, that is, the recovery of metallic lithium is achieved. The recovery rate of metallic lithium is determined to be 99.25%;
[0118] 4) After drying the water leaching residue obtained in step 2), first calculate and determine the amount of magnesium oxide to be retained based on the molar ratio of the total amount of nickel, cobalt and manganese in the target acid leaching residue after acid leaching to magnesium (1:0.1). Subsequently, add 0.4 mol / L of dilute sulfuric acid at 60°C and perform acid leaching adjustment for 2 hours; after filtering, obtain the acid leaching residue and magnesium sulfate solution that retain part of the magnesium oxide. Finally, the obtained magnesium sulfate solution is subjected to an evaporation and crystallization treatment to obtain a magnesium sulfate precipitate with a purity of 98.32%, thereby realizing the recovery and recycling of magnesium sulfate;
[0119] 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3) according to the molar ratio of Li:Ni:Co:Mn:Mg=1.05:0.5:0.2:0.3:0.1. At this time, the Ni content in the acid leaching residue is insufficient, and a small amount of nickel sulfate needs to be added to meet the above ratio. Then, in an oxygen atmosphere, it is pre-sintered at 750°C for 5h, and then heated to 900°C and sintered for 20h to obtain the regenerated ternary positive electrode active material.
[0120] It has been determined that the nickel recovery rate in this embodiment is 99.17%, the cobalt recovery rate is 98.96%, and the manganese recovery rate is 98.39%. At a current rate of 0.2C, the initial discharge specific capacity of the regenerated ternary positive electrode active material is only 123.64mAh / g, and it is 100.33mAh / g after 100 cycles. The coulombic efficiency during the cycle is 82.74%.
[0121] It should be noted that, according to the above embodiments of the present invention, those skilled in the art can fully realize the full scope of the independent claims and dependent rights of the present invention, and the implementation process and method are the same as the above embodiments; and the part not described in detail in the present invention belongs to the well-known technology in the field. However, the protection scope of the present invention is not limited to this, and any changes or substitutions that can be easily thought of by any person familiar with the field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for recycling positive electrode active materials using magnesium sulfate, characterized in that: The steps include: 1) Mix the waste lithium battery black powder, magnesium sulfate and carbon source according to n (Me) :n (MgSO4) :n (C) =1:1.2~1.8:1.8~2.5 for mixing, where n (Me) The total molar amount of nickel, cobalt and manganese in the waste lithium battery black powder is then placed in a vacuum or inert atmosphere for roasting to obtain a roasted product; the roasting temperature is 600-900°C; 2) adding the roasted product obtained in step 1) into water at a mass volume ratio of roasted product: water = 1:5-1:15 g / mL for water leaching treatment, and obtaining a lithium sulfate solution and water leaching residue after suction filtration; 3) adding the lithium sulfate solution obtained in step 2) into a saturated sodium carbonate solution to precipitate lithium to obtain lithium carbonate precipitate, thereby realizing the recovery of metallic lithium; 4) drying the water leaching residue obtained in step 2), adding dilute sulfuric acid for acid leaching, filtering to obtain the acid leaching residue and magnesium sulfate solution, and then evaporating and crystallizing the magnesium sulfate solution to obtain magnesium sulfate precipitate, thus realizing the magnesium sulfate recovery cycle; 5) The acid leaching residue obtained in step 4) is mixed with the lithium carbonate obtained in step 3), and the mixture is sintered to obtain the regenerated ternary positive electrode active material.
2. A method for recycling positive electrode active materials using magnesium sulfate according to claim 1, characterized in that: In the step 1), the components of the waste lithium battery black powder include, by mass, Ni: 15-80%, Co: 5-30%, Mn: 5-30%, Li: 2-10%, Al: 0-1%, Ca: 0-0.3%, Mg: 0-0.3%, Fe: 0-0.3%, Cu: 0-1%, and C: 0-35%.
3. The method for recycling positive electrode active materials using magnesium sulfate according to claim 1, characterized in that: In the step 1), the calcination time is 1 to 3 hours.
4. The method for recycling positive electrode active materials using magnesium sulfate according to claim 1, characterized in that: In the step 2), the water immersion treatment time is 1-3 hours and the temperature is 20-40°C.
5. A method for recycling positive electrode active materials using magnesium sulfate according to any one of claims 1 to 4, characterized in that: In the step 3), the concentration of the saturated sodium carbonate is 1.5-2 mol / L.
6. A method for recycling positive electrode active materials using magnesium sulfate according to any one of claims 1 to 4, characterized in that: In the step 4), the acid leaching treatment time is 1-3 hours and the temperature is 40-80°C.
7. A method for recycling positive electrode active materials using magnesium sulfate according to any one of claims 1 to 4, characterized in that: In step 4), the concentration of the dilute sulfuric acid is 0.2-0.6 mol / L, and the amount of the added sulfuric acid is based on the amount of n in the acid leaching residue after acid leaching. (Me) :n (Mg) =1:0.02~1:0.05, where n (Me) is the total molar amount of nickel, cobalt and manganese in the acid leaching residue. The dilute sulfuric acid can be added multiple times for adjustment according to the residual magnesium content in the acid leaching residue after acid leaching.
8. A method for recycling positive electrode active materials using magnesium sulfate according to any one of claims 1 to 4, characterized in that: In the step 5), the acid leaching residue obtained in the step 4) is mixed with the lithium carbonate obtained in the step 3) according to the molar ratio of Li:Ni:Co:Mn:Mg=1~1.1:0.5:0.2:0.3:0.02~0.
05. When the content of Ni, Co and / or Mn is insufficient, it can be supplemented by adding nickel sulfate, cobalt sulfate and / or manganese sulfate.
9. A method for recycling positive electrode active materials using magnesium sulfate according to any one of claims 1 to 4, characterized in that: In the step 5), the sintering atmosphere is an oxygen atmosphere, and the pre-sintering is first performed at 750-800° C. for not less than 5 hours, and then the temperature is raised to 900-950° C. and sintered for not less than 20 hours.
Citation Information
Patent Citations
Method for preparing ternary positive electrode material through recovering waste ternary lithium battery
CN111206148A
Recycling method of waste nickel-cobalt-manganese ternary lithium battery
CN117013128A